2016
DOI: 10.1016/j.conbuildmat.2016.03.097
|View full text |Cite
|
Sign up to set email alerts
|

Secondary aggregates and seawater employment for sustainable concrete dyke blocks production: Case study

Abstract: 11The main objective of this research work was to validate the on site real scale production of 12 dyke blocks employing coarse mixed recycled aggregates, steel slag aggregates and seawater. 13A laboratory experimental phase (Phase 1) was carried out prior to real scale concrete block 14 production within Barcelona's port (Phase 2). According to the results, the concretes 15 produced with a combined mixture of 50% coarse mixed aggregates and 50% of coarse steel 16 aggregates achieved the most adequate prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 19 publications
4
37
1
1
Order By: Relevance
“…The production of Ordinary Portland Cement (OPC) is energy-intensive and contributes to about 5-7% of total anthropogenic CO 2 emissions (Shaikh and Dobson 2019). Moreover, due to the over-exploitation of available deposits, sand and freshwater are now the two most valuable commodities of the twenty-first century (Etxeberria et al 2016a;Dhondy et al 2019). According to the United Nations (2019), over 40% of the world's population faces a scarcity of freshwater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of Ordinary Portland Cement (OPC) is energy-intensive and contributes to about 5-7% of total anthropogenic CO 2 emissions (Shaikh and Dobson 2019). Moreover, due to the over-exploitation of available deposits, sand and freshwater are now the two most valuable commodities of the twenty-first century (Etxeberria et al 2016a;Dhondy et al 2019). According to the United Nations (2019), over 40% of the world's population faces a scarcity of freshwater.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely agreed that seawater has an accelerating effect of cement hydration processes (Govindarajan and Gopalakrishnan 2011;Li et al 2018a;Younis et al 2018;Montanari et al 2019;Sikora et al 2019b) and contributes to a decrease in the setting time and workability of concrete (Etxeberria et al 2016b;Younis et al 2018;Li et al 2019;Teng et al 2019). Early strength improvement, as an effect of accelerated cement hydration, has been widely reported (Demir et al 2010;Wegian 2010;Otsuki et al 2012;Abdel-Magid et al 2016;Etxeberria et al 2016a;Li et al 2018a). After 28 days of curing, the effects of seawater in OPC-based concrete are considered to be minor and strength improvements (if at all observable) are generally limited to 5-10%, with long-term mechanical performance being reported as slightly lower than that of OPC-based concrete produced with freshwater (Mbadike and Elinwa 2011;Etxeberria and Gonzalez-Corominas 2018;Guo et al 2018;Bertola et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to use seawater to mix or cure concrete at times during infrastructure construction on islands . Previous studies have shown no significant difference in the mechanical properties of concrete when mixed and cured with seawater or freshwater . It seems feasible to apply seawater in plain concrete or concrete filled with glass fiber reinforced polymers .…”
Section: Introductionmentioning
confidence: 99%
“…In series 3 concrete a maximum of 50% of RMA (RC50-3) could be allowed for dyke block production. The use of 50% of RMA employing Portland cement for concrete production is possible when 50% of the aggregates are mixed together with 50% steel slag aggregates [21] [31].…”
Section: Dry-density Water Absorption and Permeable Porosity Testmentioning
confidence: 99%
“…In series 3 concrete a maximum of 50% of RMA (RC50-3) could be allowed for dyke block production. The use of 50% of RMA employing Portland cement for concrete production is possible when 50% of the aggregates are mixed together with 50% steel slag aggregates [21]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 7 Water absorption and permeable porosity followed similar tendencies to those of the density property, the increase in RMA replacement produced an increase in water absorption and porosity.…”
mentioning
confidence: 99%